Pengaruh Kompetensi Aparatur, Penerapan Akuntabilitas dan Ketaatan pada peraturan terhadap Akuntabilitas Kinerja pada BPKA Provinsi Aceh - Eliana Eliana; Thasrif Murhadi; Indra Kesuma; Irmawati Irmawati; Engkin Muttaqin (Jurnal Mutiara Ilmu Akuntansi, 2024)
This study aims to analyse the competence of local government apparatus, the implementation of financial accountability and compliance with regulations on performance accountability at the Aceh Financial Management Agency. The sample of this study were employees of the Aceh Financial Management Agency, totalling 29 employees using the census technique. The variable competence of local government apparatus, the application of financial accountability and adherence to regulations on performance accountability is measured using a Likert scale, and the data is obtained by distributing questionnaires to respondents. The results of the analysis show that simultaneously there is an influence of the competence of local government apparatus, the application of financial accountability and adherence to regulations on performance accountability. The results of the F test obtained Fcount> Ftabel or (16.346> 2.73) and a significant test that the p value is 0.000 < p which is set at 0.05. Partial test results show that: 1. The competence of local government apparatus affects performance accountability Thitung 3,755> Ttabel 1,703 and p value 0.001 < p 0.05 means significant. 2. The application of financial accountability affects performance accountability Thitung 2,713> Ttable 1,703 and p value 0.002 < from p 0.05 means significant, 3. Obedience to regulations affects performance accountability Thitung 2,777> Ttable 1,703 and p value 0.004 < from p 0.05 means significant.